VLSI Design of Power Gated NOR-based Content Addressable Memory - Dr.satyanarayana, Jayalakshmi Devi, (International Journal of Scientific Research and Management (IJSRM), 2017)
content addressable memory provides high speed search function in a single clock cycle.CAM is power hungry because of itsparallel match line comparison. Thus we need to design low power high speed CAM designs. In this project the high speed will beacquired by using parity bit. We introduce an effective gated power technique to reduce the peak and average power consumption. Afeedback loop is employed to auto turn off the power supply to the comparison elements and hence average power consumption by75%. The proposed design can work at supply voltage o.35v